Ubudiyah NU Guna Mencegah Ideologi Yang Gemar Menvonis Bid’ah - Nur Sahid; Muhammad Ma'shum (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2020)
This study aims to describe the NU Ubudiyah applied at Al-Ishlah Islamic boarding school and how to prevent students from ideologies who are fond of convicting heresy. This research uses a qualitative approach with a case study research design. The results stated that NU's strong ideology was tight in Indonesian society at the grassroots level. This ideology is rooted in the traditions of society. Starting from reading Yasin, Tahlil, and others that are difficult to disappear. The tradition is acculturated with the beliefs of Ancient Javanese inherited by Hindu Buddhism.